Dendritic cell-mediated HIV-1 infection of T-cells demonstrates a direct relationship to plasma viral RNA levels - Arora, Reetakshi (2010)
OBJECTIVE: To examine the relationship between infectivity of HIV-1 variants in dendritic cell-mediated in trans infection of T-cells and plasma viral RNA levels in infected subjects. METHODS: HIV-1 was isolated from PBMCs of chronically infected individuals, typed for coreceptor usage, and viral replication was examined in monocyte derived-dendritic cells-peripheral blood lymphocytes (DC-PBL) co-cultures. The rate of p24 antigen production during the logarithmic phase of viral replication was determined by ELISA. Additionally, nef variants were cloned and expressed in trans with a HIV-luciferase vector and CCR5-tropic HIV-1 envelope, and infectivity was measured in DC-mediated capture-transfer assays. RESULTS: Replication capacity of HIV-1 viral CCR5-tropic isolates in DC-PBL co-cultures was linearly associated with the plasma viral RNA levels in a cohort of HIV-1 infected individuals exhibiting an inverse relationship between plasma viral RNA and CD4 cell count. Furthermore, infectivity activity of Nef variants in context of DC-mediated enhanced infection of T-cells also showed a linear relationship to plasma viral RNA levels. CONCLUSION: These results illustrate that replication capacity of HIV-1 in DC-T-cell cultures is a significant predictor of plasma viral RNA level. The data suggest that adaptation of HIV-1 to DC interactions with T-cells influences the level of viral replication in the host.